2017
DOI: 10.1074/jbc.m116.770255
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Ruler Protein Interaction Interface on the Substrate Specificity Switch Protein in the Yersinia Type III Secretion System

Abstract: Edited by Thomas Sö llnerMany pathogenic Gram-negative bacteria use the type III secretion system (T3SS) to deliver effector proteins into eukaryotic host cells. In Yersinia, the switch to secretion of effector proteins is induced first after intimate contact between the bacterium and its eukaryotic target cell has been established, and the T3SS proteins YscP and YscU play a central role in this process. Here we identify the molecular details of the YscP binding site on YscU by means of nuclear magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
(102 reference statements)
1
15
0
Order By: Relevance
“…Recent photo-crosslinking experiments have demonstrated that the conserved core domain of FliK C directly binds to FlhB C 45 . Similar protein-protein interactions have been observed in the injectisome 55 . These suggest that length control and substrate specificity switching mechanisms are conserved in both flagellar and injectisome systems.…”
Section: Discussionsupporting
confidence: 77%
“…Recent photo-crosslinking experiments have demonstrated that the conserved core domain of FliK C directly binds to FlhB C 45 . Similar protein-protein interactions have been observed in the injectisome 55 . These suggest that length control and substrate specificity switching mechanisms are conserved in both flagellar and injectisome systems.…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown that the C-terminal domain of YscP (YscP C ), which is a FliK homologue of the Yersinia type III secretion system, directly binds to the C-terminal domain of YscU (YscU C ), which is a FlhB homologue. Ala-355 of YscU C , which corresponds to Ala-343 of FlhB CC , is critical for the binding to YscP C , and Leu-280 of YscU C , which corresponds to Ala-286 of FlhB CC , contributes to this binding (Ho et al, 2017). Ala-343 is located in helix a4, and Ala-286 is located in a loop between the b2 and b3 strands.…”
Section: Discussionmentioning
confidence: 99%
“…FlhB C is involved in the substrate specificity switching along with the molecular ruler protein FliK, which is also secreted via the flagellar type III protein export apparatus during hook assembly (Erhardt, Singer, Wee, Keener, & Hughes, ; Kutsukake, Minamino, & Yokoseki, ; Minamino, González‐Pedrajo, Yamaguchi, Aizawa, & Macnab, ; Minamino, Moriya, Hirano, Hughes, & Namba, ; Moriya, Minamino, Hughes, Macnab, & Namba, ; Shibata et al, ; Uchida & Aizawa, ; Williams et al, ). The C‐terminal domain of a FliK homologue, YscP, of the Yersinia injectisome binds to the C‐terminal cytoplasmic domain of a FlhB homologue, YscU, to promote substrate specificity switching of the virulence‐associated type III protein export apparatus (Ho et al, ). Consistently, photo‐cross‐linking experiments have showed a direct interaction between FlhB C and the C‐terminal domain of FliK (FliK C ; Kinoshita, Aizawa, Inoue, Namba, & Minamino, ).…”
Section: Introductionmentioning
confidence: 99%